Hebrews - Phillips, Richard D. (Richard Davis), 1960- (Phillipsburg, N.J. : P & R Pub., 2006)
Few studies can be more profitable to Christians today than that of the Epistle to the Hebrews, says Richard Phillips. "Written ... to a group of Jewish Christians facing persecution in the mid-first century AD, the words of this book speak to Christians everywhere about standing firm in Jesus Christ." Hebrews captures the challenges and pitfalls of people throughout the ages and shows both why and how to press on in the faith. Its message of warning and hope centers on the surpassing supremacy of Jesus, seen often from the vantage point of the Old Testament. In keeping with the Reformed Expository Commentary series, this treatment of Hebrews is accessible to both pastors and lay teachers. Each volume in the series provides exposition that gives careful attention to the biblical text, is doctrinally Reformed, focuses on Christ through the lens of redemptive history, and applies the Bible to our contemporary setting. - Publisher.
Part 1: The supremacy of Christ -- God's final word -- Prophet, priest, and king -- Superior to angels -- The reigning Lord -- Pay attention! -- His story -- Perfect through suffering -- Able to help -- The great apostle -- Part 2: Warnings against falling away -- A warning against unbelief -- Salvation lost -- The Sabbath rest -- Entering God's rest -- God's living Word -- The throne of grace -- Appointed as priest -- The source of our salvation -- From milk to meat -- Once enlightened -- Diligent to the end -- An anchor for the soul -- Part 3: Our great high priest -- Melchizedek -- A better hope -- Because He lives -- Perfectly fitting -- A superior ministry -- The new covenant -- The earthly sanctuary -- The blood of Christ -- Last will and testament -- Once for all -- The body of Christ -- A great conclusion -- Part 4: Exhortations to and examples of faith -- How should we then live? -- A dreadful punishment -- In a little while -- What is faith? -- Faith justifying -- Faith pleasing God -- Faith working -- Faith looking forward -- Faith in the promise -- Faith seeking a home -- Faith tested -- Faith trusting God's plan -- Faith choosing God -- Faith passing through -- Faith conquering -- Faith fixed on Jesus -- Part 5: Concluding exhortations -- Disciplined as sons -- A call to holiness -- The mountain of grace -- What cannot be shaken -- Jesus Christ the same -- Outside the camp -- A sacrifice of praise -- Benediction of peace.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; 2; Bible; Commentaries